CHALLENGES IN IMPLEMENTING AN INDIVIDUAL APPROACH IN TRADITIONAL EDUCATION: SYSTEMIC BARRIERS, PRACTICAL CONSTRAINTS, AND EVIDENCE-BASED PATHWAYS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
An individual approach (individualized learning, differentiated instruction, learner-centered support) is widely promoted as a way to improve learning outcomes and reduce inequities, yet its implementation in traditional education systems remains inconsistent and fragile. This article examines the key challenges that hinder individualized approaches in conventional school settings, where curriculum pacing, classroom organization, assessment regimes, and teacher workload are designed for “the average learner.” Using a structured literature-based analysis of global policy reports and large-scale international datasets, the paper synthesizes barriers at five levels: